An Examination of Day-to-Day and Intraindividual Pain Variability in Low Back Pain. Issue 10 (3rd April 2021) - Wesolowicz, Danielle M; Bishop, Mark D; Robinson, Michael E
Abstract: Objective: This study aimed to capture day-to-day changes in pain intensity in individuals with low back pain (LBP), which may be indicative of patients' ability to modulate their pain levels. A secondary aim was to explore the presence of latent subgroups characterized by pain level, intraindividual pain variability, and change in pain over a 14-day period. Subjects: Participants were 54 adults with self-reported LBP recruited from outpatient physical therapy clinics and the community. Methods: Over the course of 14 days, participants completed daily measures of pain intensity, catastrophizing, pain self-efficacy, and negative affect. Change in pain intensity as well as total amount of intraindividual pain variability were also calculated. Results: Daily increases in maladaptive coping and affective responses (i.e., higher catastrophizing, higher negative affect, lower pain self-efficacy) were associated with increases in pain intensity. A hierarchical cluster analysis revealed three subgroups: 1) moderate pain intensity, moderate pain variability, increase in pain over time; 2) low pain intensity, low pain variability, no change in pain over time; and 3) moderate pain intensity, high pain variability, decrease in pain over time. Cluster 2 demonstrated more adaptive coping and affective responses at baseline and during the 14-day period, and clusters 1 and 3 did not differ in their coping or affective responses. Conclusions: These findings provide support that day-to-day changes in pain, coping, and affective responses are meaningful and provide additional evidence of pain variability as a potential phenotypic characteristic.